2012
DOI: 10.2147/ijgm.s29197
|View full text |Cite
|
Sign up to set email alerts
|

The interactions between hemostasis and resistance training: a review

Abstract: Physical inactivity is considered a risk factor for cardiovascular disease and is strongly associated with changes in arterial structure. Regular physical activity and exercise contributes to the prevention of coronary artery disease. Therefore, cardiovascular and resistance training improve hemostatic parameters and promote a less thrombotic blood profile. This review highlights the studies, mechanisms, and outcomes relating to the effectiveness of resistance training on the process of hemostasis. The Pubmed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The use of TEG has been an important tool for the evaluation of the coagulation index in rats [ 18 , 19 ] and in this study TEG was used to assess individual hemodynamic changes in response to LPS and exercise. Moreover, our findings are consistent with previous publications that report a beneficial effect of exercise on coagulation parameters and an overall enhanced fibrinolytic state [ 47 , 49 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The use of TEG has been an important tool for the evaluation of the coagulation index in rats [ 18 , 19 ] and in this study TEG was used to assess individual hemodynamic changes in response to LPS and exercise. Moreover, our findings are consistent with previous publications that report a beneficial effect of exercise on coagulation parameters and an overall enhanced fibrinolytic state [ 47 , 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we previously demonstrated that inflammation-induced maternal hemostatic alterations, detected systemically using TEG, are comparable to hemostatic alterations detected locally at the utero-placental interface in a model of inflammation-induced fetal demise [ 18 ]. Though some studies have described a pro-thrombotic effect of high intensity exercise (>75% of VO 2max ) [ 45 , 46 ], there is evidence that exercise prevents thrombosis during hospitalization and prolonged bedtime periods in non-pregnant individuals, and that exercise improves the hemostatic profile [ 47 , 48 ]. In the present study, exercise normalized LPS-induced alterations in TEG parameters such that the values were not different from those of sedentary, saline-treated, control rats.…”
Section: Discussionmentioning
confidence: 99%
“…Blood hemostasis represents the interaction between systems controlling coagulation and fibrinolysis. It has been shown that regular exercise may positively impact the hemostatic system by balancing fibrinolytic and coagulation blood profiles in healthy individuals and patients with known diseases 1,2. Acute bouts of resistance training (RT) without blood flow restriction (BFR) in middle-aged men with coronary artery disease increased tissue plasminogen activator (tPA) and decreased plasminogen activator inhibitor-1 (PAI-1) 3.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important, as several studies have suggested that both resistance exercise as well as high-protein intake might affect the coagulation system. 4 6 For example, despite using different methodologies, studies investigating the effects of resistance exercise on the hemostatic system have consistently reported increases in t-PA levels in response to resistance training. 4 6 Data reporting the effects of high protein intake on the coagulation system are, however, contradictory at this point.…”
Section: Introductionmentioning
confidence: 99%
“… 4 6 For example, despite using different methodologies, studies investigating the effects of resistance exercise on the hemostatic system have consistently reported increases in t-PA levels in response to resistance training. 4 6 Data reporting the effects of high protein intake on the coagulation system are, however, contradictory at this point. On one hand it has been shown that high protein intake has prothrombotic effects, as it increases the fibrinogen levels 7 and decreases bleeding times.…”
Section: Introductionmentioning
confidence: 99%